2017
DOI: 10.1016/j.bpj.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Platelet Contractility and Elasticity of Fibrin/Erythrocytes in Blood Clot Retraction

Abstract: Blood clot contraction (retraction) is driven by platelet-generated forces propagated by the fibrin network and results in clot shrinkage and deformation of erythrocytes. To elucidate the mechanical nature of this process, we developed a model that combines an active contractile motor element with passive viscoelastic elements. Despite its importance for thrombosis and wound healing, clot contraction is poorly understood. This model predicts how clot contraction occurs due to active contractile platelets inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
40
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
4
40
0
1
Order By: Relevance
“…Hr10 is also distinguished from eptifibatide by its ability to preserve thrombin-induced clot retraction at equimolar concentrations that fully inhibit agonist-induced platelet aggregation. Clot retraction occurs in response to αIIbβ3-fibrin mediated actomyosin interaction 4,19 , and is thought to secure hemostasis in vivo, as evidenced by increased bleeding in mice with impaired clot retraction 43 , as well as in recipients of all three current clot-retraction inhibitory anti-αIIbβ3 drugs 18,20,37 . The underlying mechanism(s) for this unexpected difference between Hr10 and eptifibatide is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hr10 is also distinguished from eptifibatide by its ability to preserve thrombin-induced clot retraction at equimolar concentrations that fully inhibit agonist-induced platelet aggregation. Clot retraction occurs in response to αIIbβ3-fibrin mediated actomyosin interaction 4,19 , and is thought to secure hemostasis in vivo, as evidenced by increased bleeding in mice with impaired clot retraction 43 , as well as in recipients of all three current clot-retraction inhibitory anti-αIIbβ3 drugs 18,20,37 . The underlying mechanism(s) for this unexpected difference between Hr10 and eptifibatide is not entirely clear.…”
Section: Discussionmentioning
confidence: 99%
“…Activated platelets adhere to the disrupted surface and aggregate upon binding of αIIbβ3 to soluble fibrinogen 1,2 . Fibrin generated by thrombin at or near the platelet surface also binds αIIbβ3, driving clot retraction 3 , thereby consolidating the integrity of the hemostatic plug, restoring blood flow and promoting wound closure 4 . Excessive platelet activation after rupture of atherosclerotic plaques, for example, may lead to formation of occlusive thrombi, which are responsible for acute myocardial infarction and stroke, leading causes of death in developed countries 5 .…”
mentioning
confidence: 99%
“…Hr10 preserves thrombin-induced clot retraction. Clot retraction normally helps secure hemostasis in vivo as evidenced by increased bleeding in mice with impaired clot retraction 26 , or in recipients of any of the three anti-αIIbβ3 drugs 4,27,28 . We compared the effects of Hr10 and eptifibatide on thrombin-induced clot retraction in fresh human platelet-rich plasma (PRP) 29 .…”
Section: Development Of Peptide Hr10mentioning
confidence: 99%
“…When activated by several agonists, including adenosine diphosphate (ADP), thrombin, or collagen, platelets adhere to the disrupted surface, and aggregate upon binding of soluble fibrinogen (FB) or other proteins 1 to agonist-activated αIIbβ3 2 . Fibrin generated by thrombin at or near the platelet surface also binds αIIbβ3, driving clot retraction 3 , thereby consolidating the integrity of the hemostatic plug, restoring blood flow, and promoting wound closure 4 . Excessive platelet activation by agonists may lead to the formation of occlusive thrombi, which are responsible for acute myocardial infarction and stroke 5 , hemodialysis access failure 6 , early loss of kidney allograft 7 and tumor growth, and metastasis 8 .…”
mentioning
confidence: 99%
“…32 Treatment with either TNF-a or sCollagen led to significant stimulation of platelet aggregation and fibrin deposition on the surface of the endothelium, as demonstrated by increased areas of platelet coverage and fibrin deposition ( Figure 1c). Scanning electron microscopic (SEM) analysis also revealed that TNF-a pretreatment of the vascular endothelium induced formation of compact clots composed primarily of erythrocytes and platelets surrounded by a fibrin network, whereas blood treated with sCollagen formed a meshwork of complex fibrin-rich clots that contained mostly red blood cells with altered stellate morphology, which is known to be associated with the retraction of fibrin during the later stages of blood clotting 33,34 and with release of inflammatory cytokines (Figure 1d). 35 These differences in clot composition are consistent with the mechanisms of thrombosis by both agents.…”
Section: Analysis Of Thrombosis-on-chipmentioning
confidence: 99%